Use of formalin-fixed paraffin-embedded tissue and single-strand conformation polymorphism analysis for polymerase chain reaction of antigen receptor rearrangements in dogs - Kaneko, N.(Yamaguchi Univ. (Japan). Faculty of Agriculture); Tanimoto, T; Morimoto, M; Hayashi, T; Shimokawa Miyama, T; Hiraoka, H; Itamoto, K; Une, S; Mizuno, T; Okuda, M (Journal of Veterinary Medical Science, 2009)
PCR for antigen receptor gene rearrangement analysis (PARR) is a new diagnostic method for lymphoid neoplasia. In PARR using formalin-fixed paraffin-embedded tissues (PARR-FFPE), control DNA amplification was successful in only three of five samples. The formalin fixation times of the three samples were shorter than those of the others. Analysis of the formalin fixation time and DNA amplification controls suggested that a formalin fixation time of less than one week is appropriate. Additionally, application of single strand conformation polymorphism (SSCP) for PARR provided clearer results than conventional PARR in 16 unfixed tissues and three FFPE tissues. These results show that PARR-FFPE is viable for tissues with an appropriate formalin fixation time and that application of FFPE and SSCP for PARR are useful for diagnosis and retrospective study of canine lymphoid neoplasia.